Interactivity: Using Expressy to Demonstrate Expressiveness in Touch-based Interactions - Wilkinson, Gerard; Wood, Gavin; Hook, Jonathan; Nappey, Tom; Kharuffa, Ahmed; Pursglove, Bradley; Haeuser, Hendrik; Hammerla, Nils; Hodges, Steve; Olivier, Patrick (Proceedings of CHI 2016, 2016)
We present an interactivity demonstration of Expressy. A system that augments existing touchscreen devices with a variety of continuous expressive interaction capabilities, using movement data from a wrist-worn IMU. Our demonstration comprises a set of applications that show how the expressive touch interaction capabilities, offered by Expressy, can enable intuitive and meaningful interactions, in contexts including productivity, entertainment and lifestyle apps. This demo submission accompanies a full paper, describing a conceptual model of expressive touch interaction and the implementation and evaluation of Expressy.